Simulation of PUE Attack Detection using Transmitter Locations and Modulation Techniques in CRNs - Mahesh Kumar N, Siddesh G.K. (International Journal of Advanced Science and Technology, 2020)
In this research article, we present the Matlab Simulation of PUE attack conceptual development using mitigation techniques based transmitter locations with received signal strength (RSS), feature detection (FD) & power estimation method (PEM) using Power Spectral Density (PSD). We know that the growth in wireless communications has increased the demand for wireless radio spectrum to utilize many social and individual benefits. Cognitive radio is a technology that provides a possible solution for improving the spectrum efficiency by allowing opportunistic access to the spectrum for unlicensed users (CRs). In this work, we mainly focus on Primary User Emulation attack (PUEA) is one such major threat posed on spectrum sensing, which decreases the spectrum access probability. In this work, we mainly focus on Primary User Emulation attack (PUEA) & this is one such major threat posed on spectrum sensing, which decreases the spectrum access probability. We had proposed the mitigation techniques based transmitter location using received signal strength (RSS) and based on feature detection (FD), which employs a cyclostationary calculation (CC) to represent the modulation features of the user signals using a mathematical model, which was the subject of another paper.Principle of operation of the detection of the primary signal & the malicious signal transmitter during the spectrum sensing period along with the data flow diagram used for the simulation purposes for the observation of the results is presented in this context. The .m code is developed as per the proposed algorithms, the simulation is run for requisite amount of time and the simulation results are observed such asthe graphs of SCF of AWGN noise signal ; SCF of the primary user signal with FM modulation technique ; SCF of the primary user signal with FM modulation technique at SNR ∞, 3 dB and –3dB ; SCF of the Malicious user signal with QPSK modulation technique at SNR ∞, 3dB and –3 dB ; Probability of false alarm ; Probability of misdetection ; Power estimation for both proposed Localization and PSD at PUE mitigation ; Probability of false alarm and misdetection of both proposed Localization and PSD ; The localization errors and computation time of the localization system are observed. The simulation results show that the system performance of the power estimation method using PSD is better than the localization detection method using RSS in the presence of PUEA, in the other words, the results portray the effectiveness of the methodology proposed in this research paper.